Legal Analysis of the Interests of Legal Protection for Victims of Criminal Acts of Defamation Due to the Actions of Debt Collectors - Siti Handayani Herdiyanti; Alfie, Dhea; Mijan; Kurniati, Yeti; RAS, Hernawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the interests of legal protection for victims of criminal acts of defamation committed by debt collectors. Indonesian laws and regulations, such as the Criminal Code (KUHP) and the Electronic Information and Transactions Law (ITE), provide a legal basis for protecting victims, but significant challenges remain in law enforcement. Difficulties in providing evidence, lengthy legal processes, and a lack of understanding of legal rights reduce the effectiveness of existing protections. Inconsistent law enforcement is also a major obstacle. This study recommends simplifying the legal process, increasing access to legal aid, increasing legal awareness, and strengthening law enforcement to improve legal protection for victims